Female reproduction neuroendocrinology. Sterility and hyperprolactinemia 2-bromo ergocryptine and cervical factor alpha. - Ascenzo Cabello, Jorge (2015)
This work is the product of the experience gained to date regarding sterility and hyperprolactinemia, the first results were presented at a symposium held in Lima on November 29, 1979.